The Measurement of Capital. - Usher, Dan (Studies in income and wealth., 1980)
How is real capital measured by government statistical agencies? How could this measure be improved to correspond more closely to an economist's ideal measure of capital in economic analysis and prediction? It is possible to construct a single, reliable time series for all capital goods, regardless of differences in vintage, technological complexity, and rates of depreciation? These questions represent the common themes of this collection of papers, originally presented at a 1976 meeting of the Conference on Income and Wealth.